2020
DOI: 10.1038/s41467-020-17386-z
|View full text |Cite
|
Sign up to set email alerts
|

Landscape of somatic single nucleotide variants and indels in colorectal cancer and impact on survival

Abstract: Colorectal cancer (CRC) is a biologically heterogeneous disease. To characterize its mutational profile, we conduct targeted sequencing of 205 genes for 2,105 CRC cases with survival data. Our data shows several findings in addition to enhancing the existing knowledge of CRC. We identify PRKCI , SPZ1 , MUTYH , MAP2K4 , FETUB , and TGFBR2 as additional genes significantly mut… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
65
1

Year Published

2020
2020
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 64 publications
(71 citation statements)
references
References 53 publications
(77 reference statements)
5
65
1
Order By: Relevance
“…In addition, with the exception of MAPK/ERK pathway mutations that all occurred in papillary and colonic type tumors, we were unable to find relevant differences between the four ITAC histological subtypes. This seems to suggest that ITAC is a genetically homogeneous group of tumors, which contrasts with previous claims that mucinous type ITAC stands apart from the other subtypes in terms of TP53 mutation and p53 overexpression, nuclear b-catenin and E-cadherin expression, gene promotor hypermethylation and chromosomal copy number alteration profile 22 , 35 , 53 55 . Finally, mutated pathways MAPK/ERK, DNA repair, WNT and PI3K did not correlate to tumor stage, overall or disease-specific survival.…”
Section: Discussioncontrasting
confidence: 96%
See 1 more Smart Citation
“…In addition, with the exception of MAPK/ERK pathway mutations that all occurred in papillary and colonic type tumors, we were unable to find relevant differences between the four ITAC histological subtypes. This seems to suggest that ITAC is a genetically homogeneous group of tumors, which contrasts with previous claims that mucinous type ITAC stands apart from the other subtypes in terms of TP53 mutation and p53 overexpression, nuclear b-catenin and E-cadherin expression, gene promotor hypermethylation and chromosomal copy number alteration profile 22 , 35 , 53 55 . Finally, mutated pathways MAPK/ERK, DNA repair, WNT and PI3K did not correlate to tumor stage, overall or disease-specific survival.…”
Section: Discussioncontrasting
confidence: 96%
“…In spite of the histological resemblance, ITAC do not have a mutational profile similar to colorectal adenocarcinoma. Although mutations in TP53, APC, CTNNB1, PIK3CA, KRAS, and BRAF occur in both tumors, the frequency is much lower in ITAC 8 , 23 28 , 32 , 53 . In fact, our data showed a low mutation frequency in general, the most frequent being PIK3CA, found in 19% of tumors.…”
Section: Discussionmentioning
confidence: 94%
“…Sixteen to nineteen percent of CRCs are defined as hypermutated based on a high rate of somatic mutations. Two studies analyzed the occurrence of p53 mutations in non-hypermutated versus hypermutated tumors, which were defined as having more than 12 or 17 mutations per one million bases, respectively, and found that 60% of non-hypermutated CRCs harbor p53 mutations, whereas p53 mutations occurred in 20–32% of hypermutated CRCs [ 70 , 71 ]. CRCs are often classified by their genetic and epigenetic aberrations into three subtypes: chromosomal instability (CIN), CpG island methylator phenotype (CIMP), and microsatellite instability (MSI), which are not mutually exclusive [ 72 , 73 ].…”
Section: P53 Mutations In Colorectal Cancermentioning
confidence: 99%
“…The association between p53 mutations and therapy responses most likely also contributes to the worse prognosis and overall-survival of CRC patients compared to patients with wild-type p53 [ 71 , 114 ]. Progression-free and overall survival was especially poor if the tumors in addition to p53 mutations also harbored KRAS or NRAS mutations, which are frequently mutated in CRC [ 115 , 116 ].…”
Section: P53 Mutations In Colorectal Cancermentioning
confidence: 99%
“…Loss of function mutations in the MKK4 gene were reported in approximately 5% of tumours from a variety of tissues [32] . Moreover, it was recently noted as a significantly mutated gene in the colorectal cancer [33] . Based on COSMIC database, 2% of all tumours harbour MKK4 mutation, highlighting two hot-spot mutations: R134W and S184L (COSMIC v.91) [31] .…”
Section: Introductionmentioning
confidence: 99%